Mathematical logic in Latin America : proceedings of the 4th Latin America Symposium on mathematical logic - Latin-America Symposium on Mathematical Logic (4th : 1978 : Santiago de Chile); Arruda, Ayda I.; Chuaqui, R.; Da Costa, N. C. A. (Amsterdam North-Holland, 1980)
PSZJBL